Serosurvey of anti-Toxocara antibodies and risk factors in adolescent and adult pregnant women of southeastern Brazil - Priscila de Oliveira Azevedo; Susana Zevallos Lescano; Rogério Giuffrida; Louise Bach Kmetiuk; Andrea Pires dos Santos; Sriveny Dangoudoubiyam; Alexander Welker Biondo; Vamilton Alvares Santarém (Public Library of Science (PLoS), 2021)
Toxocariasis is worldwide endemic parasitic anthropozoonosis with high risk to those in in vulnerable populations and particularly during pregnancy and childhood. Although the prevalence of anti-Toxocara spp. antibodies has been extensively studied, risk factors of pregnant women of different ages remains to be established. This study was designed to i) assess the presence of anti-Toxocara spp. antibodies in pregnant women that presented to the public health system in a city of southeastern Brazil, and ii) determine the risk factors for toxocariasis in adolescent and adult pregnant women. This cross-sectional study included 280 pregnant women (71 aged up to and including 17 years [adolescents] and 209 aged 18 years and older [adults]). Pregnant women voluntarily agreed to complete a socioeconomic questionnaire and provide serum samples. Anti-Toxocara IgG antibodies were screened by Enzyme-Linked Immunosorbent Assay (ELISA). Univariable and multivariable logistic regression models were performed to assess the risks for toxocariasis. Overall, 20.7% of pregnant women were seropositive (33.8% of adolescents and 16.3% of adults). Prevalence in pregnant adolescents was 2.6-fold higher than in adults (Odds ration [OR]: 2.63; 95% CI: 1.42-4.86, p = 0.003). Multivariate analysis revealed that contact with soil (p = 0.01; OR = 4.76) and being in the first trimester of pregnancy (p = 0.03; OR = 0.17) had significantly greater risk of toxocariasis for adolescents, and attainment of elementary through middle school education level (p = 0.05; OR = 8.33) was a risk factor in adult pregnant women. Toxocariasis is likely underreported and neglected in adolescent pregnant women; this age group should always be monitored for toxocariasis and correspondent clinical signs, particularly at late pregnancy. Author summary Toxocariasis has been described as a worldwide cosmopolitan anthropozoonosis with high risk to those in in vulnerable populations and particularly during pregnancy and childhood. Although the prevalence of anti-Toxocara spp. antibodies has been extensively studied, risk factors of pregnant women of different ages remains to be established. This study was designed to assess the presence of anti-Toxocara spp. antibodies in pregnant women presented to the public health system in a city of southeastern Brazil, and determine the risk factors for toxocariasis in adolescent and adult pregnant women. Our results show that Toxocara spp. seroprevalence in pregnant women may be influenced by age; with younger age identified as a risk factor for Toxocara spp. seropositivity. Toxocariasis is likely underreported and neglected in adolescent pregnant women; this age group should always be monitored for toxocariasis and correspondent clinical signs, particularly at late pregnancy. This data may be useful as background information for educational programs on toxocariasis prevention in pregnant women, particularly adolescents.